Clinical experience of MRI4D QUASAR motion phantom for latency measurements in 0.35T MR‐LINAC. Issue 1 (18th December 2020) - Kim, Taeho; Lewis, Benjamin; Lotey, Rajiv; Barberi, Enzo; Green, Olga
Abstract: Purpose: In MRgRT, accuracy of treatment depends on the gating latency, when real‐time targeting and gating is enabled. Gating latency is dependent on image acquisition, processing time, accuracy, efficacy of target tracking algorithms, and radiation beam delivery latency. In this report, clinical experience of the MRI 4D QUASAR motion phantom for latency measurements on a 0.35‐T magnetic resonance‐linear accelerator (MR‐LINAC) with two imaging speeds and four tracking algorithms was studied. Materials/Methods: Beam‐control latency was measured on a 0.35‐T MR‐LINAC system with four target tracking algorithms and two real‐time cine imaging sequences [four and eight frames per second (FPS)]. Using an MR‐compatible motion phantom, the delays between phantom beam triggering signal and linac radiation beam control signal were evaluated for three motion periods with a rigid target. The gating point was set to be 8 mm above the full exhalation position. The beam‐off latency was measured for a total of 24 combinations of tracking algorithm, imaging FPS, and motion periods. The corresponding gating target margins were determined using the target motion speed multiplied by the beam‐off latency. Results: The largest measured beam‐off latency was 302 ± 20 ms with the Large Deforming Targets (LDT) algorithm and 4 s motion period imaged with 8‐FPS cine MRI. The corresponding gating uncertainty based on target motion speed was 3.0 mm. The range of the average beam‐off latency was 128–243 ms in 4‐FPS imaging and 47–302 ms in 8‐FPS imaging. Conclusions: The gating latency was measured using an MRI 4D QUASAR motion phantom in a 0.35‐T MR‐LINAC. The latency measurements include time delay related to MR imaging method, target tracking algorithm and system delay. The gating uncertainty was estimated based on the beam‐off latency measurements and the target motion.